Efektifitas Edukasi Kesehatan Seksual dan Reproduksi Pranikah terhadap Pengetahuan Siswa/i SMAN 1 Kakap Kubu Raya - Lidia Hastuti (Jurnal Abdimas Kesehatan (JAK), 2022)
Various efforts have been made by the government to reduce the number of young marriages, but this problem still exists. Provision of information needs to be done to increase students' knowledge about sexual/reproductive health, prevention of premarital sexual behavior and sexually transmitted infections. Provision of information can be done by providing direct information and other promotional media such as distributing leaflets. Universities can contribute to efforts to prevent the risk of young marriage by making health promotion efforts through education to students. Care for society program to increase knowledge about reproductive health, premarital sexual health, prevent risky sexual behavior and sexually transmitted infections in adolescents. Promotion efforts can be packaged by providing education with the theme of this activity being "Effectiveness of premarital sexual and reproductive health education on students' knowledge".   The implementation of education proved to be effective in increasing the knowledge of adolescents, before being given education the mean±SD 7.43±2.02, and after being given education the mean±SD 8.66±2.65. There is a difference in mean±SD before and after that is 1.23±2.06 with p-value=0.000 (p<0.05). Education is proven to increase students' knowledge about reproductive health, premarital sexual health, preventing risky sexual behavior and sexually transmitted infections. The school can coordinate with the health service center  to carry out advanced programs.